Penggunaan Media Gambar Berbasis Pendekatan Konstruktivisme untuk Meningkatkan Motivasi dan Hasil Belajar Bahasa Inggris Siswa SLBN 1 Lombok Barat - Sahwan, Sahwan (Jurnal Paedagogy, 2022)
This study aims to increase the motivation and learning outcomes of English language learning outcomes for West Lombok SLBN 1 students through the use of image media based on a constructivism approach. This research method uses classroom action research with the research subjects being 4th graders of class 7/c. This research instrument uses observation sheets, tests, and documentation. While the data analysis technique used descriptive analysis. The results of this study indicate that the use of image media based on a constructivism approach can improve motivation and learning outcomes of English students in grade 7/c SLBN 1 West Lombok in the academic year 2021/2022. This can be seen from the percentage increase in motivation and student learning outcomes in the first cycle by 25% increasing to 100% in the second cycle. In addition, the percentage of student learning completeness in the first cycle of 25% increased to 100% in the second cycle.